Estudo do efeito de substratos metamateriais em parâmetros de antenas de microfita - Barros, Vitor Fernandes de (2012)
Microstrip antennas are subject matter in several research fields due to its numerous advantages. The discovery, at 1999, of a new class of materials called metamaterials - usually composed of metallic elements immersed in a dielectric medium, have attracted the attention of the scientific community, due to its electromagnetic properties, especially the ability to use in planar structures, such as microstrip, without interfering with their traditional geometry. The aim of this paper is to analyze the effects of one and bidimensional metamaterial substrates in microstrip antennas, with different configurations of resonance rings, SRR, in the dielectric layer. Fractal geometry is applied to these rings, in seeking to verify a multiband behavior and to reduce the resonance frequency of the antennas. The results are then given by commercial software Ansoft HFSS, used for precise analysis of the electromagnetic behavior of antennas by Finite Element Method (FEM). To reach it, this essay will first perform a literature study on fractal geometry and its generative process. This paper also presents an analysis of microstrip antennas, with emphasis on addressing different types of substrates as part of its electric and magnetic anisotropic behavior. It s performed too an approach on metamaterials and their unique properties